1984
DOI: 10.1002/aic.690300220
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of short contact time coal liquefaction. Part II: Effect of nature of coal and solvent

Abstract: A bituminous coal (Powhatan No. 5 ) and a subbituminous coal (Belle Ayr) were liquefied in the presence of hydrogen donor solvents. Statistical analyses of the data showed that for contact times up to 10 min, the coal conversion, measured in terms of tetrahydrofuran solubles, was not significantly different for the two coals. However, the subbituminous coal gave more asphaltenes than the bituminous coal.The hydrogen-donating capacity of the solvent was varied by the addition of hydrogenated phenanthrene to SRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…m lt is clear that the addition of catalyst to the liquefaction reactor is advantageous, and it is not difficult to speculate as to why this is so. The insitu regeneration of hydrogen donor may be necessary to insure that free-radical coal fragments are quenched rapidly to prevent repolymerization (2,3), and it has been shown that good hydrogen donor capacity is essential to reduce solvent adduction (4)(5)(6). lt has been suggested that the catalyst may participate directly in the hydrogen transfer reactions between the hydrogen donor and the II coal fragments (7).…”
mentioning
confidence: 99%
“…m lt is clear that the addition of catalyst to the liquefaction reactor is advantageous, and it is not difficult to speculate as to why this is so. The insitu regeneration of hydrogen donor may be necessary to insure that free-radical coal fragments are quenched rapidly to prevent repolymerization (2,3), and it has been shown that good hydrogen donor capacity is essential to reduce solvent adduction (4)(5)(6). lt has been suggested that the catalyst may participate directly in the hydrogen transfer reactions between the hydrogen donor and the II coal fragments (7).…”
mentioning
confidence: 99%